Influence of Surface Treatments on the Bioactivity of Ti. (1st January 2013) - Lindahl, Carl; Engqvist, Håkan; Xia, Wei
Abstract : Several techniques have been described to modify the surface of titanium to make it more bioactive. Heat treatment (HT) and sodium hydroxide treatment (NaOH) have been used and can change the crystallinity and surface chemistry of titanium implants. However, no studies have systemically focused on comparing these different methods and their effect on the bioactivity of Ti. Therefore, in this study, Ti substrates were systematically treated using HT, NaOH, and a combination of HT and NaOH. The Ti plates were heat treated at various temperatures, and the plates were subjected to HT followed by soaking in NaOH or first soaked in NaOH and then heat treated. The morphology, crystallinity, hardness, water contact angle, and surface energy of the samples were analyzed as well as the bioactivity after immersion in PBS. Morphology and crystallinity changed with increasing temperature. The difference was most pronounced for the 800°C treated samples. The water contact angle decreased, and the surface energy increased with increasing temperature and was highest for 800°C. The rutile surface showed faster hydroxyapatite formation. NaOH treatment of the HT Ti samples increased the surface energy and improved its bioactivity further. Also, HT of NaOH samples improved the bioactivity compared to only HT.